A Voxel-Based Diffusion Tensor Imaging Study of White Matter in Bipolar Disorder - Mahon, Katie (2009)
There is evidence from post-mortem and magnetic resonance imaging studies that hyperintensities, oligodendrioglial abnormalities and gross white matter volumetric alterations play a role in the pathophysiology of bipolar disorder. There is also functional imaging evidence for a defect in frontal cortico-subcortical pathways in bipolar disorder, but the white matter comprising these pathways has not been well-investigated. Few studies have investigated white matter integrity in patients with bipolar disorder compared to healthy volunteers and the majority of studies have used manual region-of-interest approaches. In this study, we compared fractional anisotropy (FA) values between 30 patients with bipolar disorder and 38 healthy volunteers in the brain white matter using a voxelwise analysis following inter-subject registration to Talairach space. Compared to healthy volunteers, patients demonstrated significantly (p < .001; cluster size ≥ 50) higher FA within the right and left frontal white matter and lower FA within the left cerebellar white matter. Examination of individual eigenvalues indicated that group differences in both axial and radial diffusivity contributed to abnormal FA within these regions. Tractography was performed in template space on averaged diffusion tensor imaging data from all individuals. Extraction of bundles passing through the clusters that differed significantly between groups suggested that white matter abnormalities along the pontine crossing tract, corticospinal/corticopontine tracts and thalamic radiation fibers may play a role in the pathogenesis of bipolar disorder. Our findings are consistent with models of bipolar disorder that implicate dysregulation of cortico-subcortical and cerebellar regions in the disorder and may have relevance for phenomenology.